Unstressable : a practical guide to stress-free living - Gawdat, Mo; Law, Alice (St. Martin's Essentials, 2024)
"Unstressable is a handbook for those who realize stress isn't what happens to you; it's how you handle what happens to you. It's a left brainer's solution to a modern right-brain problem. Mo Gawdat is an engineer. What most of us see as inchoate, insurmountable problems he sees as systems overloads to tackle and solve. Unstressable breaks stress into inputs and effects, classifying human stressors as: stress to the mind, stress to emotions, stress to the body, and stress to the soul. Once classified, Gawdat and co-author Alice Law show readers how stress can be predicted-with mathematical certainty-and once predicted, prevented. Unstressable shows readers how most of us deal with the unpleasant, anxiety-producing and even miserable or tragic events in our lives: stress is always a by-product, leading directly to inability to cope, health problems and cratered confidence. Gawdat guides readers to no-woo-woo, all-science-based solutions. He'll train readers to: -Develop habits and attitudes of listening and learning that limit stress -Learn the language of de-stressing mind, emotions, body and soul -Respond, not react -Release self-criticism, insomnia, and lethargy -Increase energy, focus and confidence"--